Approximation Solutions for Local Fractional Schrödinger Equation in the One-Dimensional Cantorian System - Yang Zhao; De-Fu Cheng; Xiao-Jun Yang (Advances in Mathematical Physics)
The local fractional Schrödinger equations in the one-dimensional Cantorian system are investigated. The approximations solutions are obtained by using the local fractional series expansion method. The obtained solutions show that the present method is an efficient and simple tool for solving the linear partial differentiable equations within the local fractional derivative.